PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN MOTIVASI BERWIRAUSAHA TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA - Riza Azzahra; Henry Eryanto; Osly Usman (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
This study aims to determine and analyze the effect of Entrepreneurship Education and Entrepreneurial Motivation on Entrepreneurial Interests of students of the Faculty of Economics, Jakarta State University. The population used in this study were students of the Faculty of Economics, State University of Jakarta with an affordable population, namely students of the Office Administration Education study program class of 2018 – 2020 with a total population of 257 students. Using the slovin method, a sample size of 157 students was determined. The sampling technique uses simple random sampling. Data collection was carried out using a questionnaire with a Likert scale. The analysis technique used is multiple linear regression test which is operated using SPSS 26.0 software to calculate hypothesis testing. The results of the study show that (1) there is a positive and significant influence between entrepreneurship education and interest in entrepreneurship, (2) there is a positive and significant influence between entrepreneurship motivation and entrepreneurship interest and (3) there is a positive and significant influence between entrepreneurship education and entrepreneurial motivation simultaneously with an interest in entrepreneurship with the results of F count 131.873 > F table which is 3.05